Mesangial cell-binding activity of serum immunoglobulin g in patients with lupus nephritis. - Desmond Y H Yap; Susan Yung; Qing Zhang; Colin Tang; Tak Mao Chan (PLoS ONE, 2014)
In vitro data showed that immunoglobulin G (IgG) from patients with lupus nephritis (LN) could bind to cultured human mesangial cells (HMC). The clinical relevance of such binding was unknown. Binding of IgG and subclasses was measured in 189 serial serum samples from 23 patients with Class III/IV±V LN (48 during renal flares, 141 during low level disease activity (LLDA)). 64 patients with non-lupus glomerular diseases (NLGD) and 23 healthy individuals were used as controls. HMC-binding was measured with cellular ELISA and expressed as OD index. HMC-binding index of total IgG was 0.12±0.09, 0.36±0.25, 0.59±0.37 and 0.74±0.42 in healthy subjects, NLGD, LN patients during LLDA, and LN flares respectively (P = 0.046, LN flare vs. LLDA; P<0.001, for healthy controls or NLGD vs. LN during flare or LLDA). Binding of serum IgG1 to HMC was 0.05±0.05, 0.15±0.11, 0.41±0.38 and 0.55±0.40 for the corresponding groups respectively (P = 0.007, LN flare vs. remission; P<0.001, for healthy controls or NLGD vs. LN during flare or remission). IgG2, IgG3 and IgG4 from patients and controls did not show significant binding to HMC. Total IgG and IgG1 HMC-binding index correlated with anti-dsDNA level (r = 0.26 and 0.39 respectively, P<0.001 for both), and inversely with C3 (r = -0.17 and -0.45, P<0.05 for both). Sensitivity/specificity of total IgG or IgG1 binding to HMC in predicting renal flares were 81.3%/39.7% (ROC AUC 0.61, P = 0.03) and 83.8%/41.8% (AUC 0.63, P = 0.009) respectively. HMC-binding by IgG1, but not total IgG, correlated with mesangial immune deposition in LN renal biopsies under electron microscopy. Our results showed that binding of serum total IgG and IgG1 in LN patients correlates with disease activity. The correlation between IgG1 HMC-binding and mesangial immune deposition suggests a potential pathogenic significance.